2020
DOI: 10.5965/259464124215
|View full text |Cite
|
Sign up to set email alerts
|

Educação Ambiental:

Abstract: A extensão complementa a formação dos universitários propiciando a aplicação prática dos conhecimentos adquiridos nas atividades de ensino. Este trabalho teve como objetivo abordar temas abrangentes de educação ambiental envolvendo ensino-pesquisa-extensão com envolvimento de três diferentes Instituições Públicas do Município de São Gabriel, Rio Grande do Sul. O trabalho com as três Instituições Públicas (Escolas Municipais, Organização Militar e Universidade Federal do Pampa) ocorreu durante dois anos (2017-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
1
0
1
Order By: Relevance
“…Regarding the assessment of the students' environmental perception, 100% of the interviewees stated that they would participate in the Green Room Circuit again. When questioned, in each specific circuit, about which activity they most liked to participate in, it is observed that in all 14 developed circuits, the ones that returned to sustainable actions were always the ones with the lowest percentages in relation to the other activities developed, where it was noted from the 1st to the 5th, in the 10th and 12th Circuit, the percentages of activities developed are very close due to being similar themes in the sustainability theme [ there is resistance in this adhesion and reflects an unfavorable opinion of the students when compared to the other activities [7].…”
Section: Audience Of the Green Room Circuit 2021mentioning
confidence: 90%
“…Regarding the assessment of the students' environmental perception, 100% of the interviewees stated that they would participate in the Green Room Circuit again. When questioned, in each specific circuit, about which activity they most liked to participate in, it is observed that in all 14 developed circuits, the ones that returned to sustainable actions were always the ones with the lowest percentages in relation to the other activities developed, where it was noted from the 1st to the 5th, in the 10th and 12th Circuit, the percentages of activities developed are very close due to being similar themes in the sustainability theme [ there is resistance in this adhesion and reflects an unfavorable opinion of the students when compared to the other activities [7].…”
Section: Audience Of the Green Room Circuit 2021mentioning
confidence: 90%
“…Portanto, segundoNucci (1996), as praças são barreiras naturais, que além de sustentável, ajudam na diminuição da poluição sonora, da estabilização do clima, consequentemente a diminuição da temperatura e o aumento da umidade. de forma amadorística, e as necessidades urbanas a serem mitigadas passam, além do estético, pelos fatores, psicológico, econômico, social, político e da própria sustentabilidade florestal (GONÇALVES, 1999;. GONÇALVES e PAIVA, 2006).Considerando a relevância da contribuição das praças para a inter-relação das sociedades urbanas, se torna necessário a estruturação desses espaços para proporcionar maior qualidade ambiental no meio urbano.…”
unclassified